Outcomes of Expandable Prostheses for Primary Bone Malignancies in Skeletally Immature Patients: A Systematic Review and Pooled Data Analysis. Issue 6 (July 2020) - Portney, Daniel A.; Bi, Andrew S.; Christian, Robert A.; Butler, Bennet A.; Peabody, Terrance D.
Abstract : Background: Osteosarcoma and other primary bone malignancies are relatively common in skeletally immature patients. Current literature features case series with disparate complication rates, making it difficult for surgeons to educate patients on outcomes after limb salvage with expandable prostheses. This study aims to provide an update on complication rates, mortality, and functional outcomes in patients who undergo limb salvage with expandable prostheses for primary bone malignancies. Methods: A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. An exhaustive PubMed/Medline and Cochrane search of peer-reviewed published literature from 1997 to 2017 was performed, yielding a total of 1350 studies. After multiple rounds of review for inclusion and exclusion criteria, 28 retrospective studies were included. All were level IV evidence of case series and retrospective studies. Overall, this included 634 total patients and 292 patients with individual patient data. The primary outcomes studied were complication rates, mortality, and Musculoskeletal Tumor Society (MSTS) functional score. Secondary outcomes included complication rate subtypes, number of lengthening procedures, mean amount lengthened, and prevalence of limb length discrepancies. Results: A total of 292 patients with individual patient data averaged 10.1 years at the surgery and had a mean follow-up of 67 months. Two hundred sixteen patients (74%) had tumors of the distal femur. MSTS scores averaged 80.3 and overall mortality was 22%. Patients with distal femur tumors averaged 4.4 lengthening procedures and 43 mm lengthened. Leg length discrepancy (LLD) was 36% overall, which increased with longer periods of follow-up ( P <0.001). Overall complication and revision rate was 43%, increasing to 59% in patients with 5 to 10 years of follow-up, and 89% in patients with >10 years of follow-up. Minimally invasive prostheses had lower rates of complications than noninvasive prostheses ( P =0.024), specifically mechanical complications ( P =0.028), mostly because of increased rates of lengthening and device failure in the noninvasive models (21% vs. 4%, P =0.0004). Conclusions: Despite its limitations, which include entirely heterogenous and retrospective case series data, this systematic review provides clinicians with pooled summary data representing the largest summary of outcomes after reconstruction with expandable prostheses to date. This analysis can assist surgeons to better understand and educate their patients and their families on functional outcomes, mortality, and complication rates after limb-sparing reconstruction with expandable prostheses for primary bone malignancies. Level of Evidence: Level IV—retrospective case series with pooled data. Abstract : Supplemental Digital Content is available in the text.